Implementation of Diverse Approaches in Teaching History as Contributing Factors for Promoting Patriotic Values - Muhthar, Asmahani; Ahmad, Abdul Razaq; Awang, Mohd Mahzan (The journal of contemporary issues in business and government, 2021)
There are many approaches in teaching history subject in school, but which approach will be used in developing patriotism values among students. In this research, teachers act as learning managers should make systematic planning first. Such planning should be processed when writing daily lesson plans by recording strategies of various approaches. The strategies used should be appropriate to the topic to be taught and not limited to a single strategy in a teaching session. The application of the strategies that have been determined needs to be comprehensive and integrated by implementing knowledge, skills and values at once. The flexible, creative, innovative and able to strengthen the teaching and learning of teachers is the backbone of the effectiveness of this diversity approach. The ability of teachers knowing the strategies, approaches, methods and techniques in teaching patriotism values is in questions. The research is a quantitative research based on strategies, approaches, methods and techniques as independent variables, while the patriotism values as the dependent variables. The research is based on three research objective developed from literature reviews. Survey questionnaires based on independent and dependent variables is developed. The total population is 974 history teachers in Selangor state and 278 sample had been selected. The data were analyzed using descriptive and multiple regression analysis. The finding shows that the level of implementation of strategies, approaches, methods and techniques is moderate among the form 4 history teacher. It is important for teachers to equip themselves with the knowledge and skills of implementing diversify history teaching approach for high impact on patriotism values among students. The level of patriotism values among history teacher is also moderate. However, the strategies, approaches, methods and techniques are significantly influencing the history teacher preparedness on patriotism values during teaching and learning in classroom